ANALISIS EFEKTIVITAS PENGAWASAN BEA DAN CUKAI BERDASARKAN SURAT PEMBERITAHUAN JALUR MERAH DALAM RANGKA PENGAMANAN KEUANGAN NEGARA DI TEMPAT PEMERIKSAAN FISIK TERPADU GRAHA SEGARA TAHUN 2024 - Citra Novlyani; M Ronny Meliala (Jurnal Ilmu Administrasi Publik, 2025)
This study aims to analyze the effectiveness of supervision conducted by the Customs Surveillance Unit based on the Red Line Notification Letter (SPJM) in safeguarding state revenue at the Integrated Physical Inspection Facility (TPFT) Graha Segara in 2024. Supervision through SPJM is part of the risk management system implemented by the Directorate General of Customs and Excise (DJBC) to identify and inspect high-risk imported goods. However, the increasing number of SPJM issued each year poses its own challenges in implementation, including technical, administrative, coordination, and infrastructure issues. This research employs a qualitative approach using in-depth interviews with key informants, including surveillance officers, structural officials, service users, and technical trainers. Secondary data were obtained from official DJBC documents and operational data from the Main Customs and Excise Office Type A Tanjung Priok. The analysis refers to the three effectiveness indicators developed by David J. Lawless: organizational effectiveness, group effectiveness, and individual effectiveness. The findings indicate that the implementation of SPJM-based supervision at TPFT Graha Segara is generally effective, although it still faces several challenges such as limited inspection tools, lack of real-time integrated information systems, and differing standards among technical agencies. Nevertheless, DJBC has undertaken various efforts, including system digitalization, technical training enhancement, and improved inter-agency coordination. Evaluating the effectiveness of SPJM supervision is crucial to ensure that the function of safeguarding state revenue can operate optimally, efficiently, and adaptively in response to the dynamics of international trade.